Pengaruh Penggunaan Tiktok Terhadap Interaksi Sosial Antar Mahasiswa Pendidikan Kepelatihan Olahraga UNG - Djalil Taidi, Mohamad; Haryani, Meri; Deluma, Dewiyanti; Gafur Ruchban, Mohamad; Tangahu, Kelvin (Jurnal Muara Olahraga, 2025)
This study aims to analyze: (1) What is meant TikTok social media, (2) How is the behavior of mahasiswa pendidikan kepelatihan olahraga Gorontalo State University, (3) Is there an influence TikTok social media on students of the pendidikan kepelatihan olahraga Department Gorontalo University. This study quantitative descriptive method. The sample this study amounted to 175 students who were determined using the Simple random sampling technique. The independent variable in this study Tiktok social media, the dependent variable is student behavior. Data collection techniques conducting interviews, observations, and using questionnaires. The prerequisite test consists of normality and linearity tests. Analysis of research data using simple linear regression, the coefficient of determination of the T test.